RESEARCH OF ACUTE TOXITY AND ANTIPHLOGISTIC ACTION OF METHYL ETHER 5-SULPHAMOYL-N-PHENYLANTHRANYL ACID - Grygoryeva, L.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Acute toxity and antiphlogistic action of methyl ether 5-sulphamoyl-N-phenylanthranyl acid was analysed. Transfer of the molecule of methyl radical from the third position to the second (connection 10) position, or to fifth position (connection 9), as well as the change in sulphamoyl substitute of ethyl radical (connection 6-12) to an atom of hydrogen (connection 1-5) leads to decrease of acute toxity. Connection 8 (methyl ether of 5-diethylsulphamoyl-4-methyl-N-phenylanthranyl acid) was selected, its antiphlogistic action (42,1%) can be compared with the activity of diclofenac sodium. Antiphlogistic effect is realized on account of inhibition of prostaglandin-synthetase PGE1.